Personalised Task Management System For Interns - Kamilia, Julaihi (Universiti Malaysia Sarawak (UNIMAS), 2023)
An effective task management system is a software tool that allows users to create, manage and organize their tasks. It provides a centralized platform for users to collaborate and communicate, enabling them to stay on top of their tasks and deadlines. In the context of industrial training, interns and trainees can greatly benefit from using a task management system. During industrial training, interns and trainees are faced with a lot of tasks, assignments, and projects to complete. These tasks may be assigned by their supervisors, mentors, or trainers, and they must be completed on time and to a high standard. A task management system can assist in this process by providing a clear and concise overview of all the tasks that need to be completed, including deadlines, priority levels, and progress updates. By using such a system, they can keep track of their assigned tasks, set reminders and deadlines, and collaborate with their supervisors and colleagues. This helps them to stay organized, prioritize their work, and meet their goals effectively. In conclusion, a task management system can streamline the training process for interns and trainees, enabling them to make the most of their time and gain valuable experience. It allows them to stay organized, prioritize their work, and meet their goals effectively while providing a platform for collaboration and communication. This, in turn, allows trainers and supervisors to monitor the progress of their trainees and provide feedback promptly, which will help them to achieve their goals and excel in their careers.